Bibliometric Analysis of the Role of Leadership in Public Organizations using VosViewer - Daswati Daswati; Syahruddin Hattab; Musdalifa Musdalifa; Sar Salbia (International Journal of Educational Administration, Management, and Leadership, 2023)
The ever-intensifying global competition necessitates strong leadership, particularly within public organizations. Leaders must not only possess a profound understanding of complex global issues but also demonstrate the agility to navigate them. This necessitates continuous improvement of leadership knowledge and its practical application across various domains. This study employs a bibliometric analysis using Vosviewer software to examine the role of leadership in public organizations. The analysis focuses on 413 relevant journal articles published within a ten-year timeframe, ranging from 2013 to 2022. The results reveal nine distinct clusters of research themes, offering a comprehensive landscape of contemporary leadership scholarship in the public sector. Notably, the analysis identifies a relative scarcity of research on "ionic leadership." To equip future public sector leaders with a multifaceted understanding of leadership styles and their effectiveness, further investigation into diverse leadership approaches and their impact within public organizations is crucial. By delving deeper into the nuances of leadership within this complex environment, this research aims to contribute valuable insights for both leadership development and effective public service delivery. Additionally, this study can serve as a springboard for future research that explores under-investigated leadership styles, such as "ionic leadership," and their potential to enhance public service effectiveness.